Portable Solar Photovoltaic Suitcase - Qoriatul Fitriyah; Elsa Puspitasari Saragi; Nuraini Lusi; Galang Sandy Prayogo; Muhammad Prihadi Eko Wahyudi (Politeknik Negeri Batam, 2021)
This appliance is a micro-scale solar power plant intended for a temporary power source in areas affected by natural disasters in Indonesia that is portable, and is equipped with basic equipment such as a charger port and LED lights. The material used for the PV is aluminium with ceramic cooling which is designed in the form of a suitcase so that it is robust, water and fire resistant.